Faktor Kemandirian Siswa untuk Menentukan Bidang Studi Lintas Minat di SMA Negeri 4 Kota Jambi - Amalia Soleha; Nelyahardi Nelyahardi; Siti Amanah (Departement of Mathematics Education, 2023)
The purpose of this study is to know the factor of student independence level to determine the field of study viewed by the genetic factor indicator or offspring of the parent, the parenting pattern of the parent, the education system in school, and the life of the community. This research approach is descriptive research, which uses questionnaire as an instrument to collect data. Data processed processed using percentage analysis. The sample of the study used amounted to 86 students. Based on the processing results obtained the result that student independence factors based on gen indicators or parent descendants have moderate levels with a percentage of 19.23%. Student independence factors based on parent pattern indicators have a moderate level with a percentage of 28.44%. The student's independence factor based on the indicator of education system in Indonesia has a moderate level with a percentage of 22.87. And the community life system has a high level with a percentage of 29.46. The conclusion of student independence factors to determine the field of cross-interest study in SMA of Niga Jobi City's largest derived from the system of factor of life of society. With that, the independence of the students is very closely related. Guidance and counseling are attended and helpful to the development of the students themselves to help the student's business in the process of life to be done well and inventory problems facing students through the process of guidance and counseling services provided by BK teachers to client / counselor